(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse the level of VO2Max endurance of UNTAD volleyball athletes. This research method uses a quantitative descriptive method. The sample in this study was UNTAD volleyball athletes, whose number was known to be 12. While the data collection technique used a test instrument. The results of this study are based on the results of the analysis of the description of research data from the implementation of the MFT (Multistage Fitness Test). The results of the UNTAD Volleyball Athletes’ tests and measurements obtained the highest achievement at level 12 reversal 9, which is predicted to have a VO2max of 56.2, and the lowest at level 8 reversal 2, which is predicted to have a VO2max of 40.5. Overall, the VO2max level of UNTAD Volleyball Athletes shows the following classification: 2 people (17%) are in the very good category, 1 person (8%) is in the Good category, 4 people (33%) are in the moderate or fairly good category, and 5 people (42%) are in the less good category. The average VO2max ability of UNTAD Volleyball Athletes is in the less good classification. From the data that has been obtained, it can be concluded that the Analysis of VO2Max Endurance of UNTAD Volleyball Athletes is still lacking, and training still needs to be improved, so that Physical Condition can be even better.